The Tooth Supported Overdenture with Ball Attachments and Copings: A Case Report - Paulose, Anoopa; Baby, Mathews; Joy, Blessenty; Babu, Haritha (Journal of Orofacial Research, 2022)
Complete edentulism can mark the beginning of certain unwanted changes of which the mostsignificant is bone resorption. Tooth supported overdenture can enhance bone preservation,maintain proprioception and gratify the patient in terms of retention. In this article, a casereport is discussed where tooth supported overdenture with ball attachments and copings arechosen. An overdenture with attachments has shown to improve the clinical longevity of the retained teeth and thus imparts long term success in these cases.